Third Order Optical Nonlinearity Of Linear Fused Ring Dichloro-Substituent Chalcone Isomers - Abdullah, Mundzir; Zainuri, Dian Alwani; Arshad, Suhana; Razak, Ibrahim Abdul; Mohammad, Sabah M. (2019)
The third-order nonlinear optical response of halogen anthracenyl chalcone isomersin dimethyl sulphonate (DMSO) as the solvent has been studied via single beam Zscan technique at 532 nm of laser excitation wavelength. The magnitude and sign of the nonlinear refractive index, n2 and the nonlinear absorption coefficient, β were determined. It was observed from the closed aperture z-scan that the samples exhibited a self-focusing effect with a negative n2. The n2 is found to be of the order of 10−8 cm2 /W. Open z-scan results showed that both samples exhibited reverse saturable absorptions with significant β. The magnitude of β is of the order of 10-4 cm/W. Optical limiting studies shows a decrement in transmittance as a function of input fluence. Optical limiting action begins at as low as 50 kW/cm2 of focal input intensity which is ideal for low powered continuous wave laser limiting applications. These attractive third-order nonlinear properties suggest that the compound can be a good candidate for optoelectronic and photonics application.